Washing machine ownership and girls' school attendance: a cross-sectional analysis of adolescents in 19 middle-income countries - Omar Karlsson; Jan-Walter De Neve (The Journal of Economic Inequality, 2024)
Abstract Excessive work among adolescents may compromise educational development. Without home appliances, household work can take over 50~h a week and an additional 30~h when an infant is present. School-aged girls are often tasked with doing laundry, which is time-consuming and inflexible without a washing machine. We determined the association between washing machine ownership and school attendance among adolescents ages 10–19~years in 19 middle-income countries between 2000 and 2021 ( N 0.167em=0.167em1,622,514). We controlled for socioeconomic and demographic characteristics, all neighborhood-level factors, and examined differences by sex, age, household wealth, and period. No relationship between washing machine ownership and school attendance was found in most countries: However, there was a substantial association for girls in Türkiye and a small to moderate association for girls in Egypt and Albania. In Türkiye, for example, girls living in households with a washing machine had 28% (95% CI 19, 37) greater school attendance compared to girls living in households which did not. No association was observed for boys. The results suggest that household ownership of a washing machine does generally not improve school attendance among girls, except possibly in specific contexts.
Keywords: 330; School attendance; Household work; Washing machine; Middle-income countries